Delay Discounting and the Income-Food Insecurity-Obesity Paradox in Mothers - Leonard H. Epstein; Ashfique Rizwan; Rocco A. Paluch; Jennifer L. Temple (Journal of Obesity)
Food insecurity, defined as unpredictable access to food that may not meet a person’s nutritional needs, is paradoxically associated with higher BMI (kg/m2) and obesity. Research has shown delay discounting, a behavioral economic measure of the preference for immediate rather than delayed rewards, is related to higher BMI, and moderates the relationship between income and food insecurity. Based on this research, we used regression models to test whether delay discounting, consideration of future consequences, and perceived stress were atemporal mediators of the food insecurity-BMI relation in 313 mothers, controlling for demographic variables. A secondary aim was to replicate the finding that delay discounting moderates the relationship between low income and high food insecurity. Results showed that low income was associated with higher food insecurity, and higher food insecurity was associated with higher BMI. Delay discounting was the only variable that was indirectly related to both paths of the food-insecurity-BMI relation. Delay discounting accounted for 22.2% of the variance in the low-income-food insecurity-obesity relation, and the total model accounted for 38.0% of the variance. The relation between low income and food insecurity was moderated by delay discounting. These data suggest that delay discounting is a potential mediator of the relationship between food insecurity and high BMI, which suggests reducing discounting in the future could be a novel target to reduce food insecurity and help people with food insecurity to reduce their excess body weight. Trial Registration. This trial is registered with NCT02873715.